Development and Validation of a Standardized Questionnaire and Standardized Diary for Use in Integrative Medicine Consultations in Gynecologic Oncology - Hack, C. C.; Hüttner, N. B. M.; Fasching, P. A.; Beckmann, M. W. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: Use of complementary and alternative medicine (CAM) in diagnoses is not standardized and is very heterogeneous. There are few published standards on integrative medicine consultations or CAM-specific validated follow-up questionnaires. The aim of this study was to develop a standard for integrative medicine consultations, a patient questionnaire which could be used as a basis for medical decisions, and a diary to evaluate the course of the integrative therapy. Patients and Methods: Between June 2013 and September 2014 a standardized integrative medicine consultation in gynecologic oncology was developed and implemented at the Department of Gynecology and Obstetrics of Erlangen University Hospital. A standard operating procedure for consultations was developed; the necessary instruments were developed and validated. Results: Overall patient assessment of the integrative medicine questionnaire and the integrative medicine diary with regard to the time required for completion, comprehensibility, complexity and functionality was positive. Patients evaluated the standardized overall concept of the integrative medicine consultation and its instruments as suitable. Conclusion: Our team is one of the first study groups to develop, validate and publish a standard procedure for integrative medicine consultations. In future, the standard operating procedure for integrative medicine procedures of the Department of Gynecology and Obstetrics of Erlangen University Hospital could be introduced in other hospitals and certified breast cancer centers and gynecologic cancer centers. This would offer patients maximum security and a standardized quality of care in integrative medicine.
Keywords: complementary and alternative medicine (CAM); integrative medicine; naturopathic treatment; questionnaire; diary